Form of Supplement and Addition of Ionophore Effects on Steer Performance while Grazing Bromegrass – Year 2 - Jaymelynn K. Farney; Jonathan Jacquez (Kansas Agricultural Experiment Station Research Reports, 2025)
Stocker steers were grazed on bromegrass from April to end of August and were supplemented with several different types of products. Treatment structure was a completely randomized design with five treatments. Treatments evaluated included mineral only (MIN); free-choice supplementation in a block format (Mintrate 40: BLOCK); and hand-fed supplement of corn:dried distillers grains at 0.25% of body weight on a dry matter basis offered three times per week (HAND). Additionally, ionophore (Rumensin; RU) was included in one block and one hand-fed supplement. Steers were weighed every 28 days while on grass. Steers received an ultrasound scan prior to placement in a feedlot. Monthly pastures were clipped to measure biomass. Steers that were hand-fed had greater ADG and were heavier at the end of the grazing period as compared with self-fed supplementation (P = 0.02). There was no difference in ADG, total gain, or final weight based on addition or not of an ionophore (P > 0.37). Hand-fed steers tended (P = 0.07) to have greater gains and final weight as compared to mineral only steers. There was no difference in gains between steers that were self-fed protein blocks as compared to MIN (P = 0.78). The gain advantages for hand feeding were observed by 84 d of grazing (P = 0.03). Steers that were supplemented tended to have greater muscle depth than MIN (P = 0.07) while there were no differences in marbling scores (P > 0.27) nor backfat thickness (P > 0.52) between any comparisons. There was no difference in available biomass between treatment groups (P > 0.50). Hand feeding supplements to cattle results in greater performance as compared to self-fed feeds evaluated. Cost of gain (COG), based on 2024 cost of products and assuming a 20-mile delivery, calculated to the lowest COG for MIN cattle, followed by hand-fed supplements, with the most expensive being the protein blocks. During the finishing period there were no differences in total gain, ADG, dry matter intake, nor feed to gain conversion for any treatments or specific comparisons (P > 0.16). However, the steers that were hand-fed supplements on grass were heavier at 140 days on feed as compared to self-supplemented steers (P = 0.06) and there was a tendency for steers that were supplemented on grass to have heavier weights at the end of feeding than those receiving only mineral (P = 0.06). Overall, if a producer was retaining ownership of calves through both the stocker and feedlot phase, they will gain an additional 46 pounds per head by supplementing with a corn:dried distillers grains delivered daily while in the stocker period over mineral only or a self-fed protein block.
Keywords: liquid feed; pressed block; hand-fed; marbling